Tunisia : 2003 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2003)
Tunisia showed strong economic performance, low inflation, and reduced poverty owing to its sound and transparent macroeconomic policies, trade liberalization, and social policies. Executive Directors commended this development, and stressed the need to tighten monetary and fiscal policies, and accelerate structural reforms. They welcomed the banking sector reforms based on the Financial System Stability Assessment report, and the liberalization achieved by Tunisia in the context of its Association Agreement with the European Union. They also urged the authorities to introduce legislation on anti-money laundering and combating the financing of terrorism.